2021
DOI: 10.1017/s1754470x21000192
|View full text |Cite
|
Sign up to set email alerts
|

A cognitive behavioural therapy (CBT) approach for working with strong feelings of guilt after traumatic events

Abstract: This article outlines a cognitive behavioural therapy (CBT) approach to treating feelings of guilt and aims to be a practical ‘how to’ guide for therapists. The therapeutic techniques were developed in the context of working with clients with a diagnosis of post-traumatic stress disorder (PTSD); however, the ideas can also be used when working with clients who do not meet a diagnosis of PTSD but have experienced trauma or adversity and feel guilty. The techniques in this article are therefore widely applicable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Specific findings also supported the physically engaging strategies were effective in increasing certain physical abilities of these survivors, such as mobility and endurance (Gilliam, et al, 2011) and overall quality of life (Li, et al, 2013). These studies demonstrated that a cognitive-behavioral framework can be effective at improving health promoting behaviors (Cox, et al, 2005;Li, et al, 2013;Mays, et al, 2011;Young, et al, 2021). To improve on these in the future, researchers suggest that studies create more regular contacts (Gilliam, et al, 2011;Li, et al, 2013), include a greater degree of intervention (Mays, et al, 2011), and consideration for age and gender (Cox, et al, 2005).…”
Section: Behavioral Interventionsmentioning
confidence: 70%
See 3 more Smart Citations
“…Specific findings also supported the physically engaging strategies were effective in increasing certain physical abilities of these survivors, such as mobility and endurance (Gilliam, et al, 2011) and overall quality of life (Li, et al, 2013). These studies demonstrated that a cognitive-behavioral framework can be effective at improving health promoting behaviors (Cox, et al, 2005;Li, et al, 2013;Mays, et al, 2011;Young, et al, 2021). To improve on these in the future, researchers suggest that studies create more regular contacts (Gilliam, et al, 2011;Li, et al, 2013), include a greater degree of intervention (Mays, et al, 2011), and consideration for age and gender (Cox, et al, 2005).…”
Section: Behavioral Interventionsmentioning
confidence: 70%
“…The findings of this study present various implications for clinical practice concerning survivors of childhood cancer, especially with regard to their navigating late effects of their disease and treatment. This study was developed to address the many needs of this population, including general introduction and access to mental healthcare (Oeffinger, et al, 2010), interpersonal skills and unlearning of learned social isolation (Chevignard, et al, 2017), radical acceptance of traumatic events and experiences (Perloff, et al, 2019), and the provision of workable coping skills for distress tolerance (Young, et al, 2021). This study's findings suggest that the Survivor Enhanced Take-A-Breath Protocol may be a feasible and functional support strategy for survivors of childhood cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Helping mitigate practitioners' sense of guilt could be informed by Kubany's model for the understanding and treatment of trauma related guilt (Kubany & Manke, 1995 ; Young et al, 2021 ). This highlights four potential cognitive biases: hindsight‐bias (i.e., presuming that current knowledge of the outcome was known at the time of the event) ‘Now I know what happened, if I'd had that knowledge when I went back, you would do something different because you know the outcome’; responsibility (i.e., taking on all or most of the responsibility for the event) ‘this was my case and he was my patient and it was just me and I thought this is…I'm responsible for this young lad’; justification (i.e., believing there was no justification for choices taken at the time and ignoring the conditions under which you took those choices) ‘….judged and criticised for the decisions I made’; and wrongdoing (i.e., the belief that you have violated personal values) ‘dread feeling that you've done something wrong’.…”
Section: Discussionmentioning
confidence: 99%